DAMPAK SELF EFFICACY, PERCEIVED ORGANIZATIONAL SUPPORT DAN LINGKUNGAN KERJA TERHADAP EMPLOYEE ENGAGEMENT KARYAWAN CV. PAKUAJI KABUPATEN TEGAL - Wahyudi, Catur; Subroto, Setyowati (ANALISIS, 2023)
This research is a classical associative research with a quantitative approach. The sampling method used is the saturated sampling method with 42 respondents. Statistical analysis used in this study is Multiple Linear Regression analysis with the help of SPSS. The results of this study explain that self-efficacy has no effect on employee engagement. Perceived organizational support has an effect on employee engagement. The work environment has an effect on employee engagement. Together, self-efficacy, perceived organizational support and work environment have an influence on employee engagement. The implications of research that can be applied to companies are employees need to get more attention, such as providing training and giving employees the opportunity to try so that employees feel more confident at work, pay attention to the work environment for employees, especially on supporting indicators such as places of worship, canteens, room where equipment is neat and work space is clean.